Reactions among Selected Consumer Groups for a New Product on the Functional Food Market - Luboińska, Magdalena (Studia Oeconomica Posnaniensia, 2018)
The emergence of new trends in the food market, especially functional foods, may confirm and be responsible for the increase of consumer awareness and knowledge about the food sector and at the same time constitute a challenge for the entry of new products into this market. Observation of the food market shows that the pro-health value of food is often less important than the price or taste of products. Consumers who are unaware of the value of health-promoting products will not be able to rationally assess the adequacy of the price to the health benefits of consuming this product. The aim of the considerations was to obtain information about the functional food consumer, to examine the reactions and expectations of a selected group of consumers towards a new product. This analysis simultaneously promotes the need to raise consumer awareness about functional products The opinion was collected among the group of participants at a thematic conference (N = 55) and among the selected group of students (N = 57), using a diagnostic survey method. The study was conducted at the University of Economics in Wrocław and during a scientific conference in March 2018, via a questionnaire. The obtained results show that 75% of students and 60% of participants at the conference are guided by taste during shopping, while 35% of students and 55% of participants at the conference value the nutritional value of the product. At the same time, 72% of students and 67% of the conference participants expect a functional product of good taste, low price and high nutritional value. Students want to improve their general health condition, change the appearance of their skin, and conference participants expect a real impact on improving health and health claims on the labels. The studies carried out show that selected groups of consumers, despite the high level of interest in the subject of healthy food, are guided by the price and taste of the product when choosing food products. These phenomena show the need to teach the consumer what is behind the price of a healthy product. At the same time, this analysis indicates limitations in the possibilities of developing new product lines and may have practical significance for enterprises operating in this sector.